DEVELOPMENT OF LOCAL AGRICULTURAL EXTENSION SERVICE AND EMPLOYMENT OF AGRUCULTURAL EXPERTS - Petrović, Živojin; Miladinovic, Marica; Novakov, Marina (Economics of Agriculture, 2007)
Agricultural extension is one of the most important aspects on which modernization of agriculture and rural areas in Vojvodina depend. Unfortunately, in relation to the farmers needs, extension in Vojvodina is not developed enough. In Vojvodina, currently operate 13 agricultural stations and only 82 experts whose primary goal is to provide extension. Problem could be relatively successfully solved by creating local extension service consisting of agricultural experts who have lost /or will loose/ their jobs and those who were unemployed until now. Local extension service would be part of current system of agricultural stations and their extension programs.